A Quality Assessment of English Idiom Translation into Indonesian in Harry Potter and The Cursed Child - Syah, Zul Kaisar Aimar; Rasyid, Muhammad Nur Akbar; Tami, Rosmah (Elite : English and Literature Journal, 2023)
This study aims to determine the quality of idiom translation and identify strategies applied by the translator in translating English idiomatic expressions into Indonesian in Harry Potter and the Cursed Child by Jack Thorne, J.K. Rowling, and John Tiffany. In achieving these goals, this research uses mixed-method approaches. It is analyzed based on the Translation Quality Assessment (TQA) model by Nababan et al. (2012) and Baker’s theory about strategies for translating idioms (2018). Meanwhile, the data was collected through questionnaires distributed to the informants. The research finding showed that the translator applies five idiom translation strategies in 70 data. Based on the frequency, the idiom translation strategies are translation by paraphrase (58.6%), literal translation (27.1%), using the idiom with similar meaning but the dissimilar form (8.6%), using an idiom with similar meaning and form (4.3%), and translation by the omission of play of idiom (1.4%). Meanwhile, the average score for the accuracy of the translation is 2.8. The average score for the acceptability of the translation is 2,8, and the average score for readability is 2.8. Overall, the average score of the English idiom translation quality in Harry Potter and the Cursed Child books is 2,8, which indicates that the translation has good quality, in other words, most of the translation is accurate, acceptable, and easily understood by the target readers